NEXUS BETWEEN ECONOMIC GROWTH, ENERGY CONSUMPTION AND ENVIRONMENTAL DEGRADATION: EMPIRICAL EVIDENCE FROM ECONOMIC COOPERATION ORGANIZATION COUNTRIES - Ullah, Ibad; Nosheen, Misbah; Raza Shah, Kashif; Ahmad, Naveed (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
Environmental sustainability is the most important concern all over the world due to low carbon emissions. A sufficient study has been conducted about the factors that influence carbon emissions in various regions of the world, whereas ECO (Economic Cooperation Organization) countries have yet to have such literature. The goal of this study is to examine the impact of economic growth, energy consumption, trade openness, gross capital formation, and urban population on carbon dioxide emissions using panel methods. Panel data we used in this research from 1993-2019 for nine economic cooperation organisation economies. We use the different panel unit root, Cross-sectional dependency, and panel Waterland tests, especially FMOLS and DOLS. The various Panel Unit Root test outcomes demonstrate that, at 1st difference, all variables are stationary. Panel cointegration techniques like (Westerlund) verify that the entire set of variables is cointegrated. In the end, FMOLS and DOLS findings reveal that all variables, including economic growth, consumption of energy, urban population, trade openness, and urban population, have a favourable and statistically significant effect on emissions of carbon dioxide (CO2). However, gross capital formation has no statistically significant impact on emissions of carbon dioxide. The research outcome of this study helps every relevant stakeholder, particularly practitioners, environmentalists, and researchers, in developing applicable policies for the sustainability of the environment, like in the reductions in carbon dioxide emissions in the Economic Cooperation Organization.